Papermaking white mud mixture for pavement base and construction method of papermaking white mud mixture
By combining paper-making white mud, gravel and slag-based composite gelling materials, and using specific construction methods, the land occupation and pollution problems caused by white mud treatment are solved, and the resource recycling of white mud and the pavement base are realized. Improve intensity and meet the standards of first-class highways.
Patent Information
- Application Number
- CN202411635264.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The treatment method of papermaking white mud leads to land occupation and groundwater pollution, and the existing technology cannot effectively solve this environmental protection problem.
The combination of paper-making white mud, gravel and slag-based composite cementitious materials is adopted to improve the strength of the pavement base through hydration reaction, and the uniformity and cementity of the materials are ensured through construction methods such as two-stage mixing, paving and rolling.
The resource recycling of white mud has been realized, the strength and durability of the pavement base layer has been improved, the risks of land occupation and pollution have been reduced, and the use standards of first-class highways have been met.
Smart Images

Figure CN119285313A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a papermaking white mud mixture for a road surface base and a construction method thereof. Background Art
[0002] Alkali pulping black liquor is the main source of pollution in the papermaking industry. Traditional alkali recovery technology eliminates the pollution of black liquor and recovers alkali, but it also produces a large amount of alkaline waste residue: white mud. A medium-sized pulp mill produces hundreds of tons of white mud every day, which constitutes serious secondary pollution.
[0003] At present, in order to solve the problem of secondary pollution of white mud, a few large wood pulp mills (such as Jiamusi, Jilin, Qingzhou paper mills) use lime kiln calcination to regenerate white mud and produce recycled lime for recycling in causticizing. However, most pulp and paper mills treat white mud by digging pits, burying or stacking, which will cause white mud to occupy a large amount of land and may pollute soil and groundwater. Therefore, it is necessary to seek more environmentally friendly and effective white mud treatment methods. Summary of the invention
[0004] The invention aims to solve the problem that papermaking white mud occupies a large amount of land and may pollute soil and groundwater, and provides a papermaking white mud mixture for a road surface base and a construction method thereof.
[0005] The technical method of the present invention is as follows:
[0006] A papermaking mud mixture for road surface base layer, the papermaking mud mixture comprises papermaking mud, crushed stone and slag-based composite cementitious material; wherein the slag-based composite cementitious material comprises sulfur furnace slag, fly ash and volcanic ash.
[0007] Optionally, the slag-based composite cementitious material sulfur slag comes from the waste residue of sulfur refining, the fly ash comes from the waste discharged from coal-fired power plants, and the volcanic ash comes from the crushed rocks and mineral particles formed by volcanic eruptions.
[0008] Optionally, the mass ratio of papermaking white mud, crushed stone and slag-based composite cementitious material is 35-40:55-58:3-5.
[0009] Optionally, the crushed stones have three particle sizes, including 5-10 mm, 10-20 mm and 20-30 mm. The mass ratio of the 5-10 mm crushed stones, 10-20 mm crushed stones and 20-30 mm crushed stones is 6-8:40-43:8-10.
[0010] The invention also provides a construction method of a papermaking white mud mixture for a road surface base, the construction method comprising: performing two-stage mixing, spreading, rolling and curing on the papermaking white mud mixture.
[0011] Optionally, two-stage mixing uses two mixing tanks connected in series.
[0012] Optionally, a crawler-type hydraulic fully automatic paver is used for paving; wherein, a reverse blade is installed in the middle of the spiral distributor of the crawler-type hydraulic fully automatic paver, and a rubber baffle is installed in front of the scraper of the crawler-type hydraulic fully automatic paver.
[0013] Optionally, rolling uses double steel wheels, single steel wheels, or rubber wheels.
[0014] The beneficial effects of the present invention are:
[0015] 1. The present invention combines papermaking white mud, crushed stone and slag-based composite cementitious materials into a papermaking white mud mixture. Since the aluminum oxide tetrahedron and silicon oxide tetrahedron in the slag-based composite cementitious material are excited in an alkaline environment, a hydration reaction occurs with the papermaking white mud. The hydration reaction changes the internal structure of the white mud pavement base material, thereby improving the strength of the pavement base. At the same time, the sulfonic slag in the slag-based composite cementitious material can provide heat during the hydration reaction, promoting the occurrence of the hydration reaction, thereby accelerating the change of the internal structure of the white mud pavement base material, and ultimately improving the strength of the pavement base.
[0016] 2. The papermaking white mud of the present invention is waste material from papermaking, the sulfur slag is waste residue from refining sulfur, and the fly ash is waste discharged from coal-fired power plants. The above waste materials, waste residues and waste are applied to the construction of road surface base, thus realizing the recycling of resources.
[0017] 3. The present invention adopts a new construction method. First, two-stage mixing is used to solve the physical properties of papermaking white mud that it is easy to clump and agglomerate, and the problem that the white mud softens when it comes into contact with water and is difficult to disperse evenly in the mixture. Then, the paver is optimized to solve the problem of high paving coefficient of papermaking white mud base material. Finally, double steel wheels, single steel wheels, and rubber wheels are used to solve the problem that papermaking white mud cannot be effectively bonded, thereby allowing papermaking white mud to be used in first-class highways. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the experimental diagram of water addition amount of papermaking white mud in Example 1;
[0019] Figure 2 This is a graph showing the unconfined compressive strength test of papermaking white mud in Example 2. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] The invention provides a papermaking mud mixture for road surface base, wherein the papermaking mud mixture comprises papermaking mud, crushed stone and slag-based composite cementitious material, wherein the slag-based composite cementitious material comprises sulfur furnace slag, fly ash and volcanic ash.
[0022] In one embodiment, the main components of papermaking white mud are shown in Table 1.
[0023]
[0024]
[0025] It can be seen that the main component of papermaking white mud is calcium carbonate, with a small amount of sodium silicate, calcium silicate or silicon dioxide, and very small amounts of sulfur, potassium, iron, aluminum, magnesium, and other compounds. These components give it good cementing activity and strength. Therefore, slag-based composite cementitious materials are needed as modifiers in the future to reverse the hydration reaction. The hydration reaction will change the internal structure of the white mud pavement base material and improve the strength of the pavement base.
[0026] In one embodiment, the passing rate of 80μm mesh is 98.8%; it is not easy to swell in water; the activity coefficient is 27.58%; it is mainly used as an inert filler in the road base material. Through papermaking white mud, crushed stone, slag-based composite cementitious materials, the slag-based composite cementitious materials can be used as a modifier to improve the strength of papermaking white mud, thereby making the road surface smoother and more solid.
[0027] In one embodiment, the slag-based composite cementitious material sulfur slag is waste residue from sulfur refining, fly ash is waste discharged from coal-fired power plants, and volcanic ash is crushed stone and mineral particles formed by volcanic eruptions. The papermaking white mud of the present invention is waste material from papermaking, the sulfur slag is waste residue from sulfur refining, and the fly ash is waste discharged from coal-fired power plants. The above waste materials, waste residues, and waste are applied to the construction of road surface base, realizing the recycling of resources.
[0028] In one embodiment, the mass ratio of papermaking white mud, crushed stone, and slag-based composite cementitious material is 35-40:55-58:3-5. Preferably, the mass ratio of papermaking white mud, crushed stone, and slag-based composite cementitious material is 38:57:5. This ratio is to ensure the strength requirements of the pavement base. If it is lower than this ratio, the pavement base cannot meet the standards of a first-class highway. If it is higher than this ratio, the pavement base can meet the standards of a first-class highway, but it will cause unnecessary waste.
[0029] In one embodiment, for example, the mass ratio of sulfur slag, fly ash and volcanic ash may be 1-2: 1-2: 1-2. For example, the ratio may be 1: 1: 1, 1: 1.5: 1, 2: 2: 1.5, 1.5: 2: 2, etc.
[0030] In one embodiment, the crushed stone has three particle sizes. Specifically, the particle sizes include 5-10mm, 10-20mm and 20-30mm. Here, the mass ratio of 5-10mm crushed stone, 10-20mm crushed stone and 20-30mm crushed stone is 6-8:40-43:8-10, and preferably, the mass ratio of 5-10mm crushed stone, 10-20mm crushed stone and 20-30mm crushed stone is 7:41:9. Here, when crushed stones of different particle sizes are laid on the road surface, a compact structure can be formed through gradation design, thereby improving the bearing capacity and stability of the road surface. For example, 5-10mm crushed stone can provide better compactness and drainage performance, while 20-30mm crushed stone can increase the thickness and strength of the road surface. At the same time, the mixed use of crushed stones of different particle sizes can form a more uniform mixture and reduce the damage to the road surface caused by local stress concentration. This mixture can better resist the influence of vehicle loads and the natural environment and extend the service life of the road surface.
[0031] The present invention also provides a construction method of a papermaking white mud mixture for a road surface base, the construction method comprising: performing two-stage mixing, spreading, rolling and curing on the papermaking white mud mixture.
[0032] A1. Two-stage mixing
[0033] In the present invention, due to the physical properties of papermaking white mud that it is easy to agglomerate and clump, and the problem that the white mud softens in water and is difficult to disperse evenly in the mixture, a two-stage mixing production process is adopted when mixing the mixture.
[0034] Specifically, the two-stage mixing uses two mixing tanks connected in series, thereby avoiding the problem that one mixing tank cannot mix the papermaking white mud evenly.
[0035] Optionally, the mixing time is not less than 15 seconds to ensure that the mixture is mixed evenly. Preferably, a vibration mixing technology is used. It should be noted that after mixing, the white material needs to be re-mixed. When encountering serious wall sticking problems, it is necessary to clean and hit the silo wall to knock off the adhered papermaking white mud mixture.
[0036] In one embodiment, before the two-stage mixing step, the papermaking white mud is dried in a constant temperature drying oven at 45°C ± 2°C for 4 hours. This is because the water content in the papermaking white mud is relatively high, and the water content can reach up to 40%, so it needs to be dried. At the same time, after drying, the water content of each material in the field should be tested before construction every day to determine the amount of water added on that day. During the mixing production process, the amount of water added should be adjusted in time according to weather changes and the situation reflected by the previous paving. For example, when the weather is hot or the transportation distance is long, on the premise of meeting the technical performance requirements, the water content should be appropriately increased by 0.5-1 percentage point when the mixture is mixed.
[0037] In one embodiment, after the mixing step and before the paving step, a transportation step is further included.
[0038] Specifically, the transportation steps include: when the ambient temperature is higher than 30°C, the time from mixing to transportation to on-site paving shall not exceed 2 hours, and if the time exceeds 3 hours, it should be disposed of as waste; when the ambient temperature is lower than 30°C and higher than 15°C, the time from mixing to transportation to on-site paving shall not exceed 3 hours, and if the time exceeds 4 hours, it should be disposed of as waste; when the ambient temperature is lower than 15°C, the time from mixing to transportation to on-site paving shall not exceed 4 hours, and if the time exceeds 5 hours, it should be disposed of as waste.
[0039] A2. Paving steps:
[0040] Specifically, the papermaking white mud base material has a high paving coefficient and is not good for compaction, so multiple paving is adopted. If only one paving is performed according to the prior art, the paving coefficient will be higher (reaching 1.5).
[0041] In one embodiment, paving is performed using a crawler-type hydraulic fully automatic paver.
[0042] Specifically, the crawler hydraulic fully automatic paver should be equipped with an automatic leveling system and measures to prevent material segregation.
[0043] Specifically, the middle of the auger of the paver is equipped with a reverse blade to reduce longitudinal segregation. The auger should be equipped with a rubber front baffle to reduce vertical segregation during paving.
[0044] Specifically, a rubber baffle is installed in front of the paver scraper (including the widened side plate), and the height of the bottom of the rubber baffle from the top surface of the underlying layer should be no more than 10 mm.
[0045] Specifically, during the paving process, the paver has a vibrator and a rammer. The vibration frequency of the vibrator shall not be less than 30Hz, the impact frequency of the rammer shall not be less than 20Hz, and the stroke shall not be less than 6mm.
[0046] In one embodiment, the step of paving comprises:
[0047] (1) During the paving process, the speed of the paver should be kept uniform and constant, and the paving speed of the mixture should be controlled at 1.0-3.0m / min.
[0048] (2) When paving the mixture, it should be kept continuous. If the interruption time exceeds 2 hours due to some reason, transverse joints should be provided.
[0049] (3) Avoid longitudinal joints during paving. When paving in two sections, the longitudinal joints should be rolled more tightly. When longitudinal joints exist, they should be connected vertically. Slanting is strictly prohibited. When using multiple pavers for paving, the models and degree of wear of the pavers should be the same. During construction, the front and rear spacing of the pavers should not exceed 10m, and the adjacent construction sections should overlap by 30cm-40cm in the longitudinal direction.
[0050] (4) When the single-operation width of the stable layer is 11-12m, the length of each flow operation section is 300m; when the single-operation width of the stable layer is greater than 12m, the length of the operation section is shortened accordingly.
[0051] (5) A dedicated person should be assigned behind the paver to eliminate aggregate segregation and agglomeration, promptly remove segregated or agglomerated areas, and fill them with good mixed materials.
[0052] (6) For extra-wide road sections that cannot be paved mechanically, manual paving, trimming and rolling should be used simultaneously.
[0053] (7) Paving surplus materials and mixed materials lost on site should be collected and disposed of in a centralized manner and must not be discarded at will.
[0054] Here, when the present invention adopts two layers of continuous paving, when the quality of the lower layer has problems, the upper layer should be processed at the same time. Before the construction of the upper structure, the maintenance materials used in the lower layer should be thoroughly cleaned, and after the construction quality of the lower bearing layer is tested to be qualified, the upper structure layer can be paved.
[0055] A3. Rolling steps:
[0056] Since the base material of papermaking white mud pavement contains a large amount of powder (more than 40%) and the cementitious material content is only 5%, it cannot form effective bonding quickly, which may cause looseness; if the strong vibration is started too early, the water-stabilizing material has not yet been compacted and segregation may occur; the aggregate has not been completely bonded, which may cause the roller to stick.
[0057] Therefore, the present invention adopts double steel wheels, single steel wheels, and rubber wheels for rolling. The steps of rolling include:
[0058] (1) First, double steel wheels are used for rolling; during the rolling process, the double steel wheels do not vibrate when moving forward, and vibrate when moving backward;
[0059] (2) secondly, a single steel wheel is used for rolling, during which the single steel wheel is vibrated;
[0060] (3) Rub and rub the rubber wheel countless times, and the rubber wheel should be larger than 30t;
[0061] (4) Finally, double steel wheels are used for finishing.
[0062] In one embodiment, the pressing should follow the principle of first the outside and then the inside. The outside rolling should exceed the paving surface by more than 10 cm, the longitudinal direction should be serrated (minimum staggered 0.5m), and the pressing joints should be staggered in a step-like manner horizontally.
[0063] In one embodiment, a dedicated person should be assigned to direct the rolling process to prevent leakage and wheel marks. When soft and elastic phenomena occur, the mixed material in that part should be dug out in time, and the roadbed material with a moisture content that meets the design requirements should be replaced for rolling. An appropriate amount of coarse aggregate or cement can also be added and mixed evenly before compaction.
[0064] In one embodiment, during construction in hot summer weather, if the roadbed material becomes loose or shifts during the rolling process, it should be moistened by spraying water mist and stirred evenly to adjust its moisture content to the moisture content at the factory.
[0065] In one embodiment, a side form is set and fixed during rolling, and a small roller and a plate compactor are used to perform initial compaction near the form on both sides of the roadbed, and then a double steel wheel roller and a rubber wheel roller are used for compaction. Within a 30cm range of facilities such as inspection wells and curbstones, large rollers are not easy to compact, so a high-power plate compactor combined with a small roller can be used for compaction.
[0066] A4. Health care steps:
[0067] After the base material layer of papermaking white mud pavement is rolled and passed the compaction inspection, it should be covered and cured within 2 hours. The construction unit should choose the appropriate curing method based on the actual situation of the project site, which can be covered with film, impermeable geotextile, wet sand, asphalt emulsion, or watered by a sprinkler truck.
[0068] For example, watering for curing: the number of watering times per day should depend on the climate. During construction during high temperature periods, water should be sprinkled twice in the morning and afternoon. During the curing period, care should be taken to keep the surface of the stabilizing material moist at all times.
[0069] For example, film covering and curing: (1) When the weather is hot and dry, the surface moisture of the papermaking white mud base layer should be observed before covering the film. If necessary, appropriate spraying and watering can be carried out, but the surface of the stabilization layer should not be eroded. Keep the base layer moist and do not frequently cycle between dry and wet. (2) For areas with large evaporation or projects with a curing time of more than 15 days, appropriate watering should be applied during the curing process. (3) The films should be overlapped intact to avoid leaks. After the film is covered, sand and other materials should be used to form a grid-like cover. When the film is partially damaged, it should be replaced in time. (4) The film can be lifted only after curing for 1d-2d before the construction of the upper structure layer.
[0070] For example, geotextile maintenance: (1) Use permeable geotextile to cover the entire section of the stable material layer, or waterproof geotextile can be laid. (2) During the laying process, attention should be paid to the overlap between the seams, and no gaps should be left. (3) After laying the geotextile, attention should be paid to watering. The number of watering per day should depend on the climate. During construction during high temperature periods, water should be sprinkled once in the morning and once in the afternoon.
[0071] In one embodiment, the curing time should be no less than 7 days. When the average daily temperature is below 10°C, the curing time should be extended to 14 days in adverse weather conditions such as rainy season, and the total curing period should be extended to 2 days before the construction of the upper layer. Except for sprinkler trucks and small commuter vehicles, no vehicles are allowed to pass during this period, and crawler engineering vehicles are strictly prohibited from directly pressing.
[0072] In one embodiment, when cracks appear in the base layer during the curing process, after deflection detection, if the bearing capacity of the structural layer meets the design requirements, the asphalt surface layer above can be paved, or the cracks can be treated by filling the cracks. For example, filling the cracks; laying glass fiber grids or single-sided singed polypropylene anti-cracking base fabrics at the cracks; laying hot modified asphalt.
[0073] The present invention is described in detail below by way of examples and experimental examples, but these are merely examples and do not limit the present invention in any form.
[0074] Example 1 Papermaking white mud water addition experiment
[0075] Papermaking white mud (hereinafter referred to as white mud) is used as the stabilized material and is added to the cement-stabilized crushed stone mixture in the form of replacing fine aggregate with equal mass. The cement-stabilized crushed stone mixture with a white mud content of 0% is used as the control group, and the cement-stabilized siliceous slag crushed stone mixture with a white mud content of 38% is used as the test group. The white mud is added to the cement-stabilized crushed stone mixture for compaction test to obtain the optimal moisture content and maximum dry density. The proportion of each material is shown in Table 1.
[0076]
[0077] Table 1 Proportion of materials in cement-stabilized siliceous slag crushed stone
[0078]
[0079] Table 2 Compaction test data of cement papermaking white mud gravel after modifying the mix ratio
[0080] Result analysis:
[0081] like Figure 1As shown in Table 1 and Table 2, when the white mud content is 50%, the optimum moisture content of cement-stabilized white mud crushed stone is 7%. When the maximum dry density is determined by the heavy compaction method, the test result should be multiplied by a correction factor of 1.03 as the standard maximum dry density. Therefore, the maximum dry density after correction is 1.90g / cm 3 According to the compaction test results, the water content of white mud itself is relatively high, so a drying step is required during molding. The compaction test results can provide an effective reference for the amount of water added during mixture molding.
[0082] Example 2 Unconfined compressive strength test of papermaking white mud
[0083] For the white mud specimens, two mix ratios were designed. The cementitious materials of the specimens before the modified mix ratio were cement and fly ash, and the cementitious materials after the modified mix ratio were slag-based composite cementitious materials. The dosage of each component is shown in Table 3:
[0084]
[0085]
[0086] Table 3 Material ratio scheme in white mud gravel specimens
[0087]
[0088] Table 4 Unconfined compressive strength data of white mud crushed stone specimens
[0089] The 7d unconfined compressive strength data of all specimens in Table 4 were averaged and compared with the 7d unconfined compressive strength of cement-stabilized crushed stone specimens. The unconfined compressive strength data of crushed stone specimens with different mix ratios at 7d age were obtained, as shown in Table 5.
[0090]
[0091]
[0092] Table 5 7d unconfined compressive strength test results of white mud specimens and cement stabilized crushed stone specimens
[0093] As shown in Table 5, the 7d unconfined compressive strength of the modified white mud specimen is 1.5MPa higher than that of the control cement stabilized gravel specimen. For the white mud specimens with two proportions, the 7d unconfined compressive strength after the modified proportion is significantly better than that before the modified proportion, and the two proportions are different in many aspects. First, the gradation of the gravel in the two proportions is different; second, the types of cementitious materials in the two proportions are different. The cementitious materials before the modified proportion are mainly cement and fly ash, while the cementitious materials after the modified proportion are slag-based composite cementitious materials; finally, the ratio of white mud to gravel is slightly different. According to the compressive strength results, the 7d unconfined strength after the modified proportion is not only significantly better than that before the modified proportion. This shows that the combination of papermaking white mud and slag-based composite cementitious materials is conducive to the improvement of the strength of the specimens, and white mud is not suitable for cement stabilization. Therefore, the subsequent white mud specimens are formed according to the modified proportion.
[0094]
[0095] Table 6 Unconfined compressive strength of white mud specimens and cement stabilized crushed stone specimens at different ages
[0096] Results Analysis
[0097] As shown in Table 6 and Figure 2 It can be seen that during the 7th to 28th day of curing of the white mud specimens, the increase in compressive strength was not as obvious as that of the cement-stabilized crushed stone specimens and the siliceous slag specimens, and even showed a downward trend, but its early strength, especially the 7d strength, was significantly greater. This is because the combination of white mud and slag-based composite cementitious materials can quickly promote the activity of the cementitious materials, and its early hydration reaction is faster than cement, and the strength is formed faster, so the strength formation time is shorter. Papermaking white mud and slag-based composite cementitious materials are also suitable for paving roads under conditions with high requirements for early strength.
[0098] According to 4.2.4 of JTG / T F20-2015 "Technical Specifications for Highway Pavement Base Construction", before the mix ratio was modified, the test specimens were prone to falling off during molding, and the 7-day unconfined compressive strength was less than 2MPa, which did not meet the strength requirements of the pavement base. After the mix ratio was modified, the 7-day unconfined compressive strength was 5.4MPa-6MPa, and the strength increased by 3 times, which can meet the requirements of expressways and first-class highways under extremely heavy and extra-heavy traffic conditions. If other performance indicators of the test specimens meet the requirements, they can be considered for use in the base of expressways and first-class highways.
[0099] Example 3 Papermaking white mud water stability test
[0100] (1) Water stability under dry-wet cycles
[0101] The water stability test results of the white mud specimens under dry-wet cycles are shown in Table 7.
[0102]
[0103] Table 7 Dry-wet cycle test results
[0104] Results Analysis
[0105] As shown in Table 7, after 5 dry-wet cycles, the unconfined compressive strength of the white mud gravel specimens did not change much, and the water stability coefficients at 7d and 28d were 1.09 and 1.07, respectively, with no significant difference. The 7d dry-wet cycle strength of the white mud specimens was greater than that of the standard curing because the white mud had a high fine material content, a large specific surface area, and more voids, which enhanced the capillary action under the action of water. At the same time, during the curing period, the slag-based composite cementitious material was constantly reacting chemically with the white mud and aggregate, which improved the bonding properties of the mixture and promoted the enhancement of water stability. The softening coefficient was greater than 85%, and the water stability was good.
[0106] (2) Water stability under full immersion
[0107] The water stability test results of the white mud specimens under full immersion are shown in Table 8.
[0108]
[0109] Table 8 Water stability test results under full immersion
[0110] Results Analysis
[0111] From Table 8, it can be seen that the water stability coefficients of the white mud specimens under full immersion at 7d and 28d are 0.82 and 0.94 respectively, the softening coefficient is greater than 82%, and the water stability is good.
[0112] Example 4 Frost resistance of papermaking white mud
[0113] The freeze-thaw cycle test results of white mud specimens are shown in Table 9.
[0114]
[0115] Table 9 Freeze-thaw cycle test results
[0116] Results Analysis
[0117] From the data in Table 9, it can be seen that there is a large difference in the mass loss of the two white mud gravel specimens after freeze-thaw. This is because 6.25-3 had some damage on the surface before freeze-thaw, so the mass loss of this specimen after freeze-thaw was more obvious. For the strength after freeze-thaw cycles, the strength loss rates of the two white mud specimens were 29.6% and 63.0%, respectively. It can be seen that both specimens have a large strength loss, especially specimen 6.25-3. The reason is that freeze-thaw cycles will promote the growth of cracks on the surface of white mud gravel specimens, destroy the adhesion between materials, and thus damage the strength of the specimens. Finally, according to the results of the freeze-thaw cycle test, it can be seen that white mud has poor frost resistance and is not suitable for use in low temperature areas.
[0118] Example 5: Anti-scouring performance of papermaking white mud
[0119] As precipitation increases, the water stored in the void structure of the pavement will gradually increase until it is saturated. When water enters the pavement structure, if there are no vehicles passing by, it is the water stability of the pavement material discussed in the previous section, which is a static state. However, when a vehicle passes by, it can generate void water pressure on the pavement structure through dynamic loads, and this water pressure is high enough to produce a scouring effect on the base material. Repeated scouring will take away part of the base material. As time goes by, the base material is gradually washed away to form mud, and finally through the existing cracks in the pavement, forming a slurry pumping disease. Therefore, it is very necessary to test the base material for water damage under this dynamic state.
[0120] The results of the anti-scouring test are shown in Table 10.
[0121]
[0122] Table 10 Anti-scouring test results of white mud base specimens
[0123] Results Analysis
[0124] As can be seen from Table 10, when comparing the scouring mass loss rate of the two mixtures at 30 minutes, the scouring mass loss rate of the white mud gravel specimen is lower than that of the cement stabilized gravel. Because white mud is used as a stabilized material to replace 0-5mm fine material, compared with 0-5mm fine material, the white mud has a larger fineness and is easier to compact into a denser whole, and has better resistance to dynamic water scouring. White mud gravel has good water stability under dynamic water pressure, and it is estimated that it can achieve the anti-scouring performance of traditional cement stabilized gravel in actual construction.
[0125] Example 6 Papermaking white mud splitting strength
[0126] Splitting strength is to apply pressure along both sides of the diameter of the specimen, so that the longitudinal section of the specimen is subjected to vertical tensile force until the specimen is destroyed. Therefore, splitting strength is also called indirect tensile strength. Cement-stabilized crushed stone material is a semi-rigid base material. Its splitting resistance mainly comes from the mutual extrusion between crushed stones and the bonding effect produced by cement hydration reaction. When it is subjected to tension, a small deformation may cause it to crack and fail.
[0127] The splitting strength test was carried out on two mixtures of cement stabilized gravel and white mud gravel. Through the test, the splitting strength of different mixtures at 28 years old can be obtained. The splitting strength of the two mixtures in the test is shown in Table 11.
[0128]
[0129] Table 11 Splitting strength test results
[0130] Results Analysis
[0131] During the splitting process, it was found that the white mud crushed stone specimen was damaged as a crack, and did not split directly into two halves, that is, the specimen underwent particle shear failure and no bite friction. Due to the powdery structure of white mud, the specific surface area of white mud mixture is larger, and the adsorption layer is thinner when the cementitious material dosage is the same. At the same dosage, the cementitious material cannot be allowed to cover the fine aggregate, resulting in insufficient bonding capacity between some fine aggregates, so the splitting strength is low.
[0132] When designing actual roads, it is necessary to adjust the pavement structure design based on the splitting strength of the siliceous slag pavement base material so that the tensile stress at the bottom of the pavement base layer meets the design index requirements.
[0133] Example 6 Papermaking white mud environmental risk assessment experiment
[0134] The comparison of important testing indicators of leachate from papermaking white mud pavement base material with current specifications is shown in Table 12:
[0135]
[0136] Table 12 Index data of leachate from papermaking mud pavement base material
[0137] Note: Groundwater quality standard Class IV - The chemical composition of groundwater is relatively high. It is based on the quality requirements for agricultural and industrial water and a certain level of human health risk. It is suitable for agricultural and some industrial water use and can be used as drinking water after proper treatment.
[0138] It can be seen from the table that only a small amount of sensory properties and general chemical indicators of the white mud-based pavement base material exceeded the standard, and no toxicological indicators, radioactive indicators, or unconventional indicators exceeded the standard, and the environmental risks are controllable.
[0139] In summary:
[0140] (1) The particle size of papermaking white mud raw material is very fine, with a pass rate of 98.8% through an 80μm sieve. It is not easy to swell in water. Its activity coefficient is 27.58%, and it is mainly used as an inert filler in road base materials.
[0141] (2) (20% moisture content) Papermaking mud pavement base material: The optimum moisture content is 7%; the 7-day unconfined compressive strength is 5.4MPa-6MPa, which meets all pavement base strength requirements and all subbase strength requirements except for expressways / first-class highways under extremely heavy and extra-heavy traffic; the 28-day water stability coefficient after 5 dry-wet cycles is 107%, and the 28-day water stability coefficient after 5 days of full immersion is 94%, which is basically the same as the water stability of ordinary water-stabilizing layers; the scour mass loss is 0.03%, and the scour resistance is better than that of ordinary water-stabilizing layers; the residual compressive strength after freeze-thaw is 54%, which is not recommended for use in low-temperature areas; when designing the pavement, it is necessary to combine the splitting strength of the papermaking mud pavement base material to verify the tensile stress at the bottom of the pavement base layer.
[0142] (3) (20% moisture content) Only a small amount of sensory properties and general chemical indicators of the papermaking white mud pavement base material exceeded the standard, and no toxicological indicators, radioactive indicators, or unconventional indicators exceeded the standard, and the environmental risks are controllable.
[0143] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A papermaking white mud mixture for road surface base, characterized in that: The papermaking white mud mixture comprises papermaking white mud, crushed stone and slag-based composite cementitious materials; wherein the slag-based composite cementitious materials comprise sulfuric slag, fly ash and volcanic ash.
2. The papermaking white mud mixture according to claim 1, characterized in that: The slag-based composite cementitious material comprises sulfur slag from waste residue of sulfur refining, fly ash from waste discharged from coal-fired power plants, and volcanic ash from crushed stones and mineral particles formed by volcanic eruptions.
3. The papermaking white mud mixture according to claim 1, characterized in that: The mass ratio of the papermaking white mud, crushed stone and slag-based composite cementitious material is 35-40:55-58:3-5.
4. The papermaking white mud mixture according to claim 1, characterized in that: The crushed stone has three particle sizes including 5-10 mm, 10-20 mm and 20-30 mm.
5. The papermaking white mud mixture according to claim 4, characterized in that: The mass ratio of the 5-10 mm crushed stone, the 10-20 mm crushed stone and the 20-30 mm crushed stone is 6-8:40-43:8-10.
6. The construction method of the papermaking white mud mixture for road surface base according to any one of claims 1 to 5, characterized in that: The construction method comprises: The papermaking white mud mixture is mixed, spread, rolled and cured in two stages.
7. The construction method according to claim 6, characterized in that: The two-stage mixing adopts two mixing cylinders connected in series.
8. The construction method according to claim 6, characterized in that: The paving is carried out using a crawler-type hydraulic fully automatic paver; wherein a reverse blade is installed in the middle of the spiral distributor of the crawler-type hydraulic fully automatic paver, and a rubber baffle is installed in front of the scraper of the crawler-type hydraulic fully automatic paver.
9. The construction method according to claim 6, characterized in that: The rolling adopts double steel wheels, single steel wheels and rubber wheels.
Citation Information
Patent Citations
White-mud base permeable brick and preparation method thereof
CN108911622A
All-solid-waste road traffic stone concrete and preparation method of all-solid-waste road traffic stone
CN115385647A
Near-full-solid-waste semi-rigid base layer and laying method thereof
CN118930198A
Improvements in and relating to the treatment of paper mill wastes
GB434225A